2019
DOI: 10.3892/mmr.2019.10504
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the hyperplasia suppressor gene inactivates airway fibroblasts obtained from a rat model of chronic obstructive pulmonary disease by inhibiting the Wnt signaling pathway

Abstract: The present study aimed to investigate the effects of hyperplasia suppressor gene (HSG) overexpression on the activation of airway fibroblasts in a rat model of chronic obstructive pulmonary disease (COPD) and assess the underlying molecular mechanisms. The rat model of COPD was established by injection of papain and confirmed by hematoxylin and eosin staining. Airway fibroblasts were identified using immunofluorescence, and HSG expression was facilitated by an HSG vector. Cell viability, apoptosis and the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We have previously reported that hyperplasia suppressor gene (HSG) overexpression inactivated airway broblasts from COPD by inhibiting the Wnt signaling pathway (51). In this study, we also provided in vivo data showing that AJ in different doses ameliorated airway remodeling and antagonized Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We have previously reported that hyperplasia suppressor gene (HSG) overexpression inactivated airway broblasts from COPD by inhibiting the Wnt signaling pathway (51). In this study, we also provided in vivo data showing that AJ in different doses ameliorated airway remodeling and antagonized Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 70%
“…Using the cultured airway broblasts obtained from COPD model, we further veri ed that Wnt agonists LiCl and HLY78 promoted the cell proliferation and reduced apoptosis. We could speculate that the antagonists of Wnt signaling pathway would block the cell proliferation and promote apoptosis, like the effect of HSG overexpression (51). Additionally, MAPK pathway agonists also exhibited the similar functions as Wnt signaling pathway agonists.…”
Section: Discussionmentioning
confidence: 89%
“…Pulmonary emphysema is related to inflammation [4,5] and cell senescence, which subsequently leads to pneumocyte death and degradation of the extracellular matrix (ECM) [6][7][8]. On the other hand, peribronchial fibrosis is mainly a response to the process of epithelial-mesenchymal transition (EMT) mediated by the disruption of the lung cell basement membrane, and it is widely regulated by the transforming growth factor β (TGF-β) signaling pathway [9,10]. Interestingly, regardless of the etiology and molecular mechanisms underlying these pathological changes, metalloproteinases, a family of zinc-dependent endoproteinases, have a predominant role in both processes: these molecules have been reported to be some of the major effector enzymes of COPD lung tissue remodeling [11].…”
Section: Introductionmentioning
confidence: 99%
“…Gelatinase B also plays a regulatory role in inflammation and fibrosis by catalyzing the activation of important molecules, such as pro-tumor necrosis factor-α (TNF-α) [24], pro-interleukin 1β (IL-1β) [25] and pro-TGF-β [26]. Additionally, MMP-9 has also been associated with mechanisms of COPD perpetuation [27], lung cancer progression [9,10], and acute exacerbations of COPD (AE-COPD), characterized by worsening of lung function and increased susceptibility to respiratory infections [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…65 In fibroblasts, hyperplasia suppressor gene (HSG) is found to inhibit airway remodeling in COPD by inhibiting the Wnt pathway and reducing beta-catenin expression to reduce cell viability. 66 Reduced levels of DKK1, an endogenous inhibitor of Wnt, are seen as more positive changes in lung function in COPD patients. 67 Studies show that in primary human airway smooth muscle cells, activation of Wnt/beta-catenin signaling pathway participates in TGF-beta-induced ECM protein deposition, including increased expressions of collagen I, fibronectin, multifunctional proteoglycan, laminin, and core proteoglycan, providing new insights for the occurrence and development of airway remodeling in lung diseases.…”
mentioning
confidence: 99%